Subthalamic Stimulation-Induced Forelimb Dyskinesias Are Linked to an Increase in Glutamate Levels in the Substantia Nigra Pars Reticulata - Boulet, Sabrina (J Neurosci, 2006)
The neurobiological mechanisms by which high-frequency stimulation of the subthalamic nucleus (STN–HFS) alleviates the motor symptoms of Parkinson's disease (PD) remain unclear. In this study, we analyzed the effects of STN–HFS on motor behavior in intact or hemiparkinsonian rats (6-hydroxydopamine lesion of the substantia nigra pars compacta) and investigated the correlation between these effects and extracellular glutamate (Glu) and GABA levels, assessed by intracerebral microdialysis in the substantia nigra pars reticulata (SNr). STN–HFS at an intensity corresponding to the threshold inducing contralateral forelimb dyskinesia, increased Glu levels in the SNr of both intact and hemiparkinsonian rats. In contrast, STN–HFS at half this intensity did not affect Glu levels in the SNr in intact or hemiparkinsonian rats but increased GABA levels in hemiparkinsonian rats only. STN–HFS-induced forelimb dyskinesia was blocked by microinjection of the Glu receptor antagonist kynurenate into the SNr and facilitated by microinjection of a mixture of the Glu receptor agonists AMPA and NMDA into the SNr. These new neurochemical data suggest that STN–HFS-induced forelimb dyskinesia is mediated by glutamate, probably via the direct activation of STN axons, shedding light on the mechanisms of STN–HFS in PD.